Perception of Built Environment and Its Association with Physical Function Among Older Adults in Maiduguri Metropolis, Nigeria: A Cross-Section Study - Ishaku, Cornelius M.; Onundi, Munirat B.; Karaga, Mahmud A.; Ajuji, Chungsyn C.; Zaki, Desmond A.; Audu, Anthony M.; Fidelis, Francis (African Journal of Medicine, Surgery and Public Health Research, 2025)
Introduction: Ageing is associated with decline in muscle mass and strength which compromise functions and participation. Physical function is a good indicator of overall health status as it lowers the risk of falls, chronic diseases and disability among older adults. Aims: To investigate the association between physical function and the perception of built environment among older adults in Maiduguri Metropolis. Methods: A cross-sectional survey was conducted to recruit apparently 400 healthy older adults aged 60 years and above, using a multi-stage random sampling technique. Descriptive statistics of mean, standard deviation and percentage were used to summarize the socio-demographics; physical function and perception of built environment among the participants. Logistic regression was used to examine the association between physical function and access to destination; social environment; neighbourhood infrastructure; aesthetic quality; and neighbourhood safety. Data was analysed using SPSS version 22 at an alpha level 0.05. Results: Most participants were males (68.8 %), living in low-income area (70.0 %) with average age of 68.77 6.52 and mean score of 83.30 ± 25.96 physical function. There was no statistically significant association found between physical function and perception of the built environmental variables among the participants, however, 3 out of the five built environment features are likely to improve physical functions. Conclusion: Although there was no significant association, access to destination in the neighbourhood, neighbourhood aesthetic quality and social environment were positively associated with the physical function. The findings of the study should be interpreted with caution as more that 70% of the participant fall in the category of those living in low-income area which may affect their built environment.